Evolving supernova remnants in multiphase interstellar media - Villagran Azuara, Marco Adrian (2020)
We performed three-dimensional magnetohydrodynamic simulations to study the evolution of a supernova remnant (SNR) in a turbulent neutral atomic interstellar medium. The media used as background shares characteristics with the Solar neighbourhood and the SNR has mass and energy similar to those of a Type Ia object. Our initial conditions consist of dense clouds in a diluted medium, with the main difference between simulations being the average magnitude of the magnetic field. We measured amplifications of the magnetic energy of up to 34 per cent, and we generated synthetic maps that illustrate how the same object can show different apparent geometries and physical properties when observed through different lines of sight.